(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study was conducted to assess the level of health culture and some related factors of the elderly people with hypertension at Da Nang C Hospital in 2019. Subjects and methods: A cross-sectional study was conducted with a sample size of 513 elderly people with hypertension treated at Da Nang C Hospital from January 2019 to May 2019. Results: The overall health culture score was 25.3 ± 5.9; the rate of limited health culture accounted for 91.8%. Some factors related to health culture included age, education level, concomitant chronic diseases and current health status (p < 0.05). Conclusion: The rate of limited health culture of elderly people with hypertension in the study area was high. Old age, low education level, concomitant chronic diseases and poor current health were positively related to health culture of elderly people.